2022
DOI: 10.12973/ejper.5.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Family Needs Studies: Relationships with Parent, Family and Child Functioning

Abstract: <p style="text-align: justify;">Findings from a research synthesis of the relationships between family needs and parent, family, and child functioning are reported. The synthesis included 31 studies conducted in 12 different countries. The studies were conducted between 1987 and 2021 and included 4,543 participants. Eight different family needs scales or adaptations of the scales were completed by the study participants (mothers, fathers, or grandmothers of children with developmental disabilities, autis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…A series of meta-analyses have been conducted to determine if measures of the four different family systems intervention components are related to variations in parent, family, and child functioning. This has included meta-analyses of family needs studies (Dunst, 2022b), family resources studies (Dunst, 2021d(Dunst, , 2021e, 2022d, family support studies (Dunst, 2022a(Dunst, , 2022c, family strengths studies (Dunst, 2021b;2021c;Dunst, Serrano, et al, 2021), and family-centered help-giving practices studies (Dunst, Trivette, & Hamby, 2007, 2008. The caregivers in the studies in the meta-analyses were primarily mothers but also included fathers and grandmothers of children and adolescents with and without identified disabilities or chronic health conditions.…”
Section: Meta-analytic Evidencementioning
confidence: 99%
“…A series of meta-analyses have been conducted to determine if measures of the four different family systems intervention components are related to variations in parent, family, and child functioning. This has included meta-analyses of family needs studies (Dunst, 2022b), family resources studies (Dunst, 2021d(Dunst, , 2021e, 2022d, family support studies (Dunst, 2022a(Dunst, , 2022c, family strengths studies (Dunst, 2021b;2021c;Dunst, Serrano, et al, 2021), and family-centered help-giving practices studies (Dunst, Trivette, & Hamby, 2007, 2008. The caregivers in the studies in the meta-analyses were primarily mothers but also included fathers and grandmothers of children and adolescents with and without identified disabilities or chronic health conditions.…”
Section: Meta-analytic Evidencementioning
confidence: 99%
“…The BASICS was designed to fill a need for a brief scale that would capture kinship caregivers' and adoptive parents' perception of their family's need for services. Existing validated scales (e.g., see Dunst, 2022) were found to be too long and lacked validation with kinship or adoptive families. The Family Needs Scale (Dunst et al, 1987) was the only identified measure that had some initial testing with kinship families (Lee et al, 2016) but its 41-item structure deemed it too burdensome for the type of participant engagement that OhioKAN intended to foster.…”
Section: Self-identified Family Needsmentioning
confidence: 99%